P407 Real-world safety of tofacitinib in inflammatory bowel diseases: a multi-centre study. (25th January 2019) - Yarur, A; Bixuan, L; Deepak, P; Khatiwada, A; Christophi, G; Ciorba, M; Ungaro, R; Fenster, M; Dimopoulos, C; Syal, G; Hirten, R; Colombel, J-F; et al.
Abstract: Background: Our aim was to examine adverse events (AEs) during real-world usage of tofacitinib in inflammatory bowel diseases (IBD). Methods: A multi-centre cohort was assembled across six tertiary IBD centres in the US. Data on demographics, IBD-specific variables, concomitant medications and AEs (including herpes zoster [HZ], hyperlipidaemia and leukopoenia) were collected. AEs were defined as serious AE if life-threatening, resulting in a hospitalisation, disability or discontinuation of therapy. Abnormal lipid profile was defined as total cholesterol 200 mg/dl, LDL 130 mg/dl, HDL <40 mg/dl or triglycerides 150 mg/dl. Results: A total of 140 IBD patients were analysed, 125 with UC, 11 Crohn's disease (CD) and 4 IBD unclassified. Median age of the cohort was 36 years (interquartile range (IQR), 26–46) with a majority of males (77, 55%) and median follow-up 75.5 days (IQR, 49.8–124.5). A majority of patients (133, 95%) were initiated at 10 mg twice a day (bid) dose with 102 (72.9%) continuing therapy to date. Nineteen patients experienced an AE; of which, 8 (42.1%) were serious AE resulting in discontinuation of therapy: 5 with HZ, 2 with leukopoenia, and 1 with increased urinary frequency/incontinence. There were no significant differences in baseline characteristics between those with or without an AE (Table 1). Five patients (3.6%) initiated on 10 bid dose developed HZ at median age 30 years (range 16–47) and median time from initiation of Tofacitinib of 7 weeks (range, 5–24). Three of these patients were female while 2 each were African-American and Hispanic and 1 was Caucasian. Three of the 5 patients were on concomitant steroids and none had received Shingrix vaccine. The HZ was single-dermatome in 4 and multi-dermatome in 1 patient. One hundred and nine patients (77.9%) had baseline lipid levels checked with 73 (52.1%) having it repeated at Week 8. Nine out of 49 patients (18.4%) with previously normal lipids had abnormal lipids at 8 weeks of treatment at 10 mg twice a day (bid), 4 of whom were initiated on a statin. Other AEs reported include rash (1 patient) and joint pain (1 patient). Sixteen patients underwent surgery (4 CD, 12 UC) within 4 weeks of last dose of Tofacitinib. Five patients required readmission within 30 days of surgery (3 UC, 2 CD). Four patients (3 UC, 1 CD) had an infection within 30 days of surgery. No post-operative thrombotic complications or reoperations occurred within 30 days of surgery. Conclusions: The safety profile of tofacitinib in IBD looks similar in real life to what has been observed in clinical trials. No new safety signal was detected.